2016
DOI: 10.1021/acs.joc.6b02220
|View full text |Cite
|
Sign up to set email alerts
|

Tetra- and Pentacationic Electrophiles and Their Chemistry

Abstract: A tetracationic electrophile has been generated in superacid and shown to undergo an arylation reaction with benzene. A cyclization product is also obtained in the absence of benzene, presumably from a tricationic intermediate. Using low-temperature NMR, the tetracationic species is directly observed from a FSOH-SbF-SOClF solution. Similar chemistry is described with a system involving penta- and tetracationic intermediates. These highly ionized structures and their chemistry were also examined by DFT calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Presumably, compound 10 is formed as a mixture of meso and dl stereoisomers. Similar reaction products were observed in our studies of tri-, tetra-, and pentacationic systems [1112]. This product, 10 , is the result of charge migration involving the carbocation center and the phenyl group (vide infra).…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Presumably, compound 10 is formed as a mixture of meso and dl stereoisomers. Similar reaction products were observed in our studies of tri-, tetra-, and pentacationic systems [1112]. This product, 10 , is the result of charge migration involving the carbocation center and the phenyl group (vide infra).…”
Section: Resultssupporting
confidence: 78%
“…Protonation of the hydroxy groups leads to immediate ionization and formation of the carbocation centers. For related conversions, computational and experimental data indicated that the protonated hydroxy groups (oxonium ions) are not persistent intermediates, but rather cleavage of the carbon–oxygen bond is almost instantaneous [12]. It is assumed that ionization to the carbocations occurs in a stepwise process, first providing pentacation 13 then the hexacation 14 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research group has studied a class of superelectrophiles in which very high levels of cationic charge are formed on the ion, including tri-, tetra-, penta-, and hexacationic structures [ 47 , 48 , 49 ]. Thus, compound 45 reacts in superacid with benzene to provide compound 46 in good yield, as a product from remote functionalization ( Scheme 12 ) [ 48 ]. In the absence of benzene, the cyclization product 47 is obtained in 79% yield.…”
Section: New Types Of Superelectrophilesmentioning
confidence: 99%
“…12 For example, pyridyl ketone (18) undergoes cyclization in the presence of CF 3 SO 3 H to provide the pyridylsubstituted indene (19) in 76% yield (Scheme 6). The chemistry is assumed to go through the dicationic carboxonium ion (20) which leads to the indene. Similar conversions were accomplished with pyrimidine, imidazole, oxazole, thiazole, quinoline, and benzothiazole systems (70-98% yields).…”
Section: Scheme 4 Schemementioning
confidence: 99%